Agricultural Co-operatives in the western world: A bibliometric analysis. (10th November 2020) - Luo, Jianli; Han, Huiying; Jia, Fu; Dong, Hao
Abstract: Since the establishment of one of the early co-operatives in Western Europe in the 1800s, co-operatives in the Western world have developed exponentially and played essential roles in improving agricultural sustainability. Much research has been carried out on this topic; however, to date, there is no systematic review of this body of the literature. To fill this gap, this paper is designed to identify the main research themes regarding agricultural co-operatives in western countries, and subsequently shed light on avenues for future research in this field. Based on a systematic literature review with bibliometric techniques including citation and co-citation analyses, this study identifies six predominant themes (social and environmental performance of co-operatives, governance structures of co-operatives, trust and commitment in co-operatives, comparisons between co-operatives and investor-owned firms (IOFs), financing problems in co-operatives, and women's co-operatives) of debates on western co-operatives. Recommendations for future research are finally provided.